The Disparity in Judge's Decisions in Forced Defense Cases - Nur Amalia Katili; Dian Ekawaty Ismail; Suwitno Yutye Imran (Estudiante Law Journal, 2022)
This study aims to analyze the chronology of cases of forced defense decisions. Normative research methods using statutory research approaches and case approaches and analytical techniques used to process legal materials are legal hermeneutics. The results of this study indicate that the decisions 794/Pid.B/2014/PN.Llg and No.257/Pid.B/2015/PN.Sky has fulfilled the elements of the noodweer requirement, namely that defense is coercive, what is being defended is oneself ), there was a very imminent threat of an imminent attack at that time, and that attack was against the law. has also fulfilled the element of the principle of subsidiarity which is the benchmark for forced defense. The disparity of decision No. 794/Pid.B/2014/PN.Log and the decision No. 257/Pid.B/2015/PN.